Managing Fragmented Database Using BVAGQ-AR Replication Model - Ainul Azila, Che Fauzi; Noraziah, Ahmad; Tutut, Herawan; Z., Abdullah; Gupta, Ritu (American Scientific Publishers, 2017)
One of the mechanisms for managing data is replication since it improves data access and reliability. However, the amount of various data grows rapidly since technology is widely available at a low-cost. Problem arises when the database is packed with data, but it has lacked of knowledge. If the unreasonable data is used in database replication, it will cause waste of data storage and delay the time taken for a replication process. This paper proposes a new algorithm namely Binary Vote Assignment on Grid Quorum with Association Rule (BVAGQ-AR) to handle fragmented database replication. BVAGQ-AR algorithm is capable of partitioning the database into disjoint fragments. Handling fragmented database replication becomes challenging issue to administrator since the distributed database is disseminated into split partitions or fragments. This paper will discuss about how to build reliable system by using the proposed BVAGQ-AR algorithm for distributed database fragmentation. The result shows that managing fragmented database replication through proposed BVAGQ-AR algorithm able to preserve data consistency.